Everyday space, mobile subjects and place-based belonging in suburban Sydney. - Williamson, Rebecca (Journal of Ethnic & Migration Studies, 2016)
In the contemporary age of international migration, the mobilities of people into and out of cities are increasingly diverse. Correspondingly, it has been claimed that forms of belonging are becoming increasingly flexible, strategic and characterised by multiple place attachments. This paper examines these claims in empirical detail by investigating how different scales of belonging and mobility come together in the context of migrant incorporation processes in a hyperdiverse, transitional suburban locality in Sydney, Australia. Drawing on several migrant biographies, I flesh out the lived dimensions of mobility and emplacement and the various routes and roots that characterise cities of diversity. This article uses grounded portrayals of individual experiences of place and everyday mobility across a range of migration statuses and ethnic backgrounds to examine the spatial practices of belonging for mobile (and relatively immobile) migrant subjects in the city. As such, this work contributes to research that highlights the mutual constitution of place and movement, by considering the role of migrants in the everyday production of urban space.